(untitled) (Islamic Sciences Journal, 2023)
This research aims to know the method that Al-Sabouni has adopted and followed in deducing the endowed remains, through the collection and study of the endowed antiquities, which he inferred in his interpretation of Surat Al-Baqarah, Al-Imran, Al-Nisa, and Al-Ma’idah, and the impact of these hadiths in his interpretation of the noble Surahs, through applied models, and from. It is obvious that every scholar has jurisprudence and inferences that he may not have been correct in, as he is a human being who makes mistakes and is correct, and the interpretation of al-Sabouni, despite his fame, indicates that he did not receive the modern study worthy of his fame.